SENSORY CHARACTERISTICS OF LOCAL CHEESE FROM THE PČINJA DISTRICT AS A POTENTIAL FOR GASTRO - TOURIST OFFERS - Stošić, Tamara; Šmugović, Stefan; Ivanović, Velibor; Kalenjuk Pivarski, Bojana; Stošić, Tijana (The Business of Tourism, 2023)
: Cheese is one of the most used foods in the world. Each region has a large number of different types of cheese that are specific in their sensory characteristics. In Serbia, the local production of homemade cheeses has a centuries-long tradition and is an important part of the country’s culinary heritage. Local cheeses that are produced all over Serbia represent an important part of our country’s gastronomic and tourist offer. Knowledge of the sensory characteristics of local cheeses is crucial for the preservation and promotion of these products. Precisely for this reason, the main subject of this paper is the sensory evaluation of four local cheeses from the Pčinj district, in the south of Serbia. Sensory evaluation of quality was carried out by trained tasters, who had the task of evaluating the potential they have for the development of the gastronomic and tourist offer of this region. Four different types of cheese, with different tastes, smells and structures, were selected for the research. The main goal is to show the sensory characteristics of cheeses, in order to be able to notice the differences in their intensity of smell, bitterness and saltiness, as well as to evaluate their influence on the level of gastronomic and tourist offer of the Pčinj district.